Preterm birth does not increase the risk of developmental dysplasia of the Hip: a systematic review and meta-analysis - Amirhossein Ghaseminejad-Raeini; Parmida Shahbazi; Ghazale Roozbahani; Amirmohammad Sharafi; Seyyed Hossein Shafiei; Yousof Fallah; Soroush Baghdadi (BMC, 2023)
Abstract Background The purpose of this systematic review was to appraise the literature on the association between preterm birth and developmental dysplasia of the hip (DDH). Methods Medline, Embase, Scopus, and Web of Science databases were queried for all studies pertaining to DDH and preterm birth. Data were imported and analyzed in Revman5 and Comprehensive Meta-Analysis (CMA) for pooled prevalence estimation. Results Fifteen studies were included in the final analysis. There were 759 newborns diagnosed with DDH in these studies. DDH was diagnosed in 2.0% [95%CI:1.1-3.5%] of the premature newborns. Pooled incidence rate of DDH was not statistically different between those groups (2.5%[0.9%-6.8%] vs. 0.7%[0.2%-2.5%] vs. 1.7%[0.6%-5.3%];Q = 2.363,p = 0.307). Conclusions In this systematic review and meta-analysis, we did not find preterm birth to be a significant risk factor for DDH. Data suggests that female sex and breech presentation are associated with DDH in preterm infants, but the data is scarce in the literature.